Upaya Meningkatkan Keterampilan Berbicara Text Procedure Dengan Metode Demonstrasi Melalui Media Benda Realia pada Siswa MTSN 10 Bireuen - Syarfiah Syarfiah (Dinasti Research, 2022)
There are problems in the ability to speak skills, especially text procedures for students at MTsN 10 Bireuen. The problem that often occurs in learning is that students are not fluent in speaking English due to limited vocabulary, grammar, speech and understanding and students lack self-confidence. This study aims to improve the ability to speak text procedure through the application of the demonstration method through the media of realia objects in class IX 4 MTsN 10 Bireuen odd semester of the 2022/2023 academic year. This type of research is Classroom Action Research (CAR) with four steps of planning (planning), action (action), observation (observation), and reflection (reflection). Data collection was carried out using observation, questionnaires, interviews, tests, and documentation. The results of the Classroom Action Research showed that there was an increase in the speaking skills of class IX 4 students at MTsN 10 Bireuen after applying the demonstration method through the media of realia objects. The learning completeness of class IX 4 semester 1 students at MTsN 10 Bireuen after using the demonstration method through realia objects in mastering the text procedure speaking skills increased from cycle I 71.68 to 77.97 in cycle II.